PENGARUH RENDAM AIR HANGAT DENGAN KENCUR TERHADAP PENURUNAN EDEMA KAKI PADA IBU HAMIL TRIMESTER KETIGA - Mardliyana, Nova Elok (Sinar : Jurnal Kebidanan, 2024)
Objective: Pregnant women will often experience discomfort during their pregnancy. The increase in complaints will increase as the gestational age increases. Foot edema is one form of change during pregnancy and discomfort that is a complaint for pregnant women. Foot edema is caused by excessive fluid clotting in the tissue system. The way to overcome this problem is to massage the foot and soak them in warm water mixed with kaempferia galanga. Foot massage can minimize swelling by applying direct pressure to the part of the body that is experiencing edema. Soaking in warm water mixed with kaempferia galanga affects recovery and can overcome swelling and cramps in pregnant women. This research aims to understand and determine the effect of theraphy foot massage and soaking in warm water mixed with kaempferia galanga on foot edema in pregnant women. Methods: The method used in this research is the systematic literature review method using the Google Scholar and Research database. The procedure for collecting articles is from quantitative research journals from the last ten years and has a minimum index of Sinta 5. Articles from research journals are searched using the keywords “foot edema and pregnant women and foot massage and soak warm water kaempferia galanga.” After the article you are looking for matches, they keyword appears; it is then selected again so that five articles are found. Results: Of the five articles, most of the disscuss the influence and application of foot massage and soaking in warm water mixed with kaempferia galanga on foot edema in pregnant women, and the results of the research show that there is an effect of foot massage and soaking in warm water mixed with kaempferia galanga to reduce foot edema in pregnant women. Conclusion: From the research it can be concluded that foot massage and soaking in warm water mixed with kaempferia galanga have an effect on reducing foot edema in pregnant women.